Assessment of quality of life determinants in hemodialysis patients of a developing country: A cross-sectional study during ongoing COVID-19 pandemic. Issue 31 (5th August 2022) - Asghar, Muhammad Sohaib; Ahsan, Muhammad Nadeem; Mal, Pooran; Tahir, Muhammad Junaid; Yasmin, Farah; Abbasher Hussien Mohamed Ahmed, Khabab
Abstract : Background and Objectives: Patients of end-stage renal disease are prone to have a very low quality of life (QoL). Variety of factors influence the QoL among sufferers of chronic kidney disease comprising of type of dialysis, sufficiency/adequacy of dialysis, and associated burden of disease. We conducted this study amidst the pandemic to determine the associated factors for poor QoL in hemodialysis patients during the ongoing pandemic. Patients and Methods: This cross-sectional study was conducted in a hemodialysis unit of a tertiary care hospital. A total of 118 participants responded to the validated questionnaire of Quality of Life Index-dialysis version-III (QLI). Higher scores signify good QoL, total scores are further categorized into subgroups desirable, relatively desirable and undesirable. Results: The mean age of the participants was 57.36 ± 10.03 years and mean body mass index of 26.73 ± 5.54 kg/m 2 . The mean total QoL of the study population was found quite low (12.99 ± 5.89). Majority of respondents fell in undesirable category of QoL (49.2%). Total QoL ( P = 0.004) and subscale health/functioning ( P = 0.003) were significantly lower in females. All the subscales along with total QoL scores were found lower in twice-weekly dialyzed patients ( P < 0.001). Marital status ( P = 0.049) and twice-weekly dialysis ( P < 0.001) were found significant with undesirable QoL. On multivariate analysis, significant determinants of undesirable QoL were twice-weekly dialysis ( P = 0.001), catheter access ( P = 0.034), phosphate ( P = 0.005) and uric acid ( P = 0.006). Conclusion: Inadequate dialysis due to lesser frequency per week leading to poorly cleared toxic substances were most significant contributors of poor QoL in our study.